Provocations for Boundary Spanning from Mohammad Nagar's Community Toilet. (November 2020) - Singh, Vanshika
Collaborative research endeavours, such as the 'Boundary Spanning and Intermediation for Urban Regeneration' project, can help unpack boundary spanning from the viewpoint of communities in informal settlements who engage with the state through certain actors operating as their citizen–state interface. This article builds on the story of a community toilet in Mohammad Nagar settlement in Bholakpur, a neighbourhood in the southern Indian city of Hyderabad, where solid consumer waste is processed, recycled and regenerated with value. Tracing the struggles to build a functional community toilet from 2012 to 2017 amidst a gentrifying real estate landscape, this article asks: what does the process of working through a fragmented community to claim a community toilet from the state say to the idea of boundary spanning? By describing the boundary-spanning activities of three different actors invested in working through a divided settlement to co-produce an effective claim, it seeks to enquire about the different knowledge types these actors hone. How are these knowledge types generated? How do different actors deploy them in the neighbourhood? Through its analysis of the post-2017 scenario, when the toilet stood built but unmaintained and unused, the article argues for studying boundary spanning over time and spatial change, especially in places like Mohammad Nagar, where securing basic and usable civic infrastructure relies on multiple iterations of boundary-spanning activities.